Original paperRacial and socioeconomic disparities in the selection of prostate brachytherapy - Schreiber, David; Chen, Shan-Chin; Rineer, Justin; Weiss, Jeffrey; Rotman, Marvin; Schwartz, David (Journal of Contemporary Brachytherapy, 2013)
Purpose: To utilize the surveillance, epidemiology, and end results database to analyze whether there are racial or socioeconomic disparities associated with the selection of prostate brachytherapy. Material and methods: We selected patients who were diagnosed with localized prostate cancer between 2004-2006 and who underwent treatment with radiation. Data regarding race and estimates of socioeconomic status were also obtained by analyzing the average reported cost of living adjusted income in the SEER county from which the patient was treated, and dividing these results into quartiles. Multivariate logistic regression analysis was used to determine whether there were any disparities associated with brachytherapy use. Results : A total of 38 704 patients were included in the analysis. Most patients (57%) received EBRT alone, while the remaining 43% of patients had brachytherapy as a component of their treatment, either alone (30.2%) or in combination with EBRT (12.2%). On multivariate logistic regression, prostate brachytherapy use was less likely in African American patients with an odds ratio of 0.89 (95% CI: 0.84-0.95, p < 0.001), and was more likely to be used in those with higher socioeconomic status. Regarding socioeconomic status, the odds ratio for receiving brachytherapy was 1.65 (95% CI: 1.55-1.75) for the 25-50% quartile, 1.92 (95% CI: 1.81-2.04) for the 50-75% quartile, and 2.05 (95% CI: 1.93-2.18) for the 75-100% quartile, respectively (p < 0.001). Conclusions : There do appear to be socioeconomic and racial disparities in the selection of prostate brachytherapy. These findings may have both significant equality of care as well as cost of care implications.